Chemistry Teachers’ Understanding of Literacy and Learning Skills as Part of 21st Century Skills: A Quantitative Descriptive Analysis - Syarifah Meutiah Eka Sari; Burhanudin Milama; Ni Pt. Pande Mirah Surya Dewi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Teachers play a crucial role in equipping students with 21st-century skills. Chemistry teachers' understanding of these competencies, particularly literacy and learning skills, is essential in shaping how they integrate them into classroom practice. This study explores the level of understanding chemistry teachers have regarding literacy and learning skills as core components of 21st-century skills. This study used a quantitative descriptive approach, using a questionnaire as its instrument. The questionnaire consisted of 44 questions covering aspects of literacy skills and learning skills. Data were obtained from 52 alums of the Chemistry Education Study Program at UIN Syarif Hidayatullah Jakarta who currently work as chemistry teachers. Data analysis was conducted using descriptive statistics to assess the teachers' level of understanding in each domain and sub-aspect. Findings indicate that chemistry teachers' understanding of literacy and learning skills falls within the good category (74.1%) based on the average score across all measured aspects. In learning skills, the highest level of understanding was observed in communication and collaboration (72.4%), while critical thinking scored the lowest (69.4%). Regarding literacy skills, understanding was highest in information literacy (79.2%) and lowest in media literacy (75.2%). These results indicate that chemistry teachers have a good understanding of 21st-century skills, although critical thinking and media literacy skills still need improvement. Therefore, it is hoped that there will be a targeted development program for chemistry teachers to strengthen these weak skills.